ANALISIS KEMAMPUAN BERPIKIR KRITIS PADA MATERI PERSAMAAN GARIS LURUS DIKAJI BERDASARKAN HABITS OF MIND - Putri Putri; Edy Yusmin; Dwi Astuti (UNIVERSITAS TANJUNGPURA, 2021)
Habits of mind are one of the many factors that influence mathematical critical thinking skills. The purpose of this study was to describe students' mathematical critical thinking skills on straight line equation material studied based on habits of mind. The results obtained: 1) There are 3 categories of habits of mind that appear, namely 29.73% high categories with the ability to think critically mathematically can provide statements in the form of reasons; evaluates gradient values; make a statement and consider it; provide a coherent and detailed explanation; set the strategy to be used, 51.35% of the medium category with the ability to think critically in mathematics can provide a statement in the form of reasons; evaluates gradient values; make a statement and consider it; just write down the steps without explanation on the written test; have a strategy to solve the questions but not according to the indicators and 18.92% low category with the ability to think critically mathematically can give statements in the form of reasons evaluates gradient values, but calculations are wrong; unable to make a statement and consider it; just write down the steps without explanation; do not have a strategy to solve the problem. Keywords: Critical Thinking, Habits Of Mind, Straight Line Equations